Proctosigmoiditis and coeliac disease. Issue 8 (August 1978) - Ansaldi, N; Santini, B; Dell'olio, D; Levis, F
Abstract : Of 80 children with proved coeliac disease, 2 presented with an associated disease of the distal portion of the large intestine. In one child the family history and the extension, localisation, and characteristics of intestinal lesions made us suspect ulcerative colitis; in the other we made a diagnosis of milk-induced colitis.